Hospital characteristics associated with trauma outcomes - Bowman, Stephen M (My University, 2006)
Trauma is the leading cause of death among Americans younger than 45 years. Regional and state trauma care systems have been developed to reduce the mortality attributable to severe injuries. Trauma care systems can reduce the preventable trauma death rate by as much as 30% for patients who reach the hospital alive. While trauma system evaluations typically assess overall trauma care between states with and without organized trauma systems, minimal attention has been given to the components that may account for observed differences.This dissertation examined trauma systems by focusing on three specific aims: (1) to evaluate the hospital characteristics associated with pediatric splenic injury management practices (splenectomy vs. spleen-conserving practice), (2) to examine the association between race/ethnicity and in-hospital mortality in patients with moderate to severe traumatic brain injury (TBI) and utilization of post-acute rehabilitation services for survivors of severe TBI, and (3) to examine rural trauma care and the impact of hospital trauma designation on in-hospital mortality and likelihood of transfer after admission.Secondary data from the Healthcare Cost and Utilization Project (Kid's Inpatient Database and the National Inpatient Sample) and the American College of Surgeons (National Trauma Data Bank) were examined using multivariable logistic regression to identify associations between trauma outcomes and hospital characteristics, adjusting for patient, injury and hospital characteristics.This dissertation produced significant results. First, splenectomy was found to be more likely among children treated at general hospitals than among children treated in children's hospitals and more common among children treated at for-profit general hospitals than in not-for-profit general hospitals. Compared to White for traumatic brain injury, Blacks were more like to die in level II hospitals, while Asians and Hispanics were more likely to die in both level I and II hospitals. Compared to Whites, Blacks and Hispanics also appeared less likely to be discharged to a rehabilitation service from either level I or II hospitals.This dissertation identified opportunities for trauma system improvement in the areas of pediatric spleen management, racial/ethnic disparities in traumatic brain injury outcomes, and rural trauma care.
Thesis (Ph. D.)--University of Washington, 2006.
Keywords: Theses--Health services